Compaction characteristics of asphalt mixture with different gradation type through Superpave Gyratory Compaction and X-Ray CT Scanning. (30th December 2016) - Zhang, Chen; Wang, Hainian; You, Zhanping; Yang, Xu
Highlights: The proper compaction temperature of asphalt mixture was investigated and recommended. Microstructure of asphalt mixture was characterized based on X-ray CT. Asphalt viscosity has a visible influence on the compaction level and VMA. The volumes of voids are mainly distributed from 0 to 150 mm 3 ranges. Abstract: To determine the appropriate compaction parameters of different asphalt mixtures (AC13, AC16, AC20 and SMA13) in Shaanxi Province and to study their micro-structural characteristics, SK70# and SK90# matrix asphalt and limestone were used in this study to prepare asphalt mixtures via Superpave Gyratory Compaction (SGC) and X-Ray CT Scanning. The compaction characteristics of these specimens were tested at three temperatures (120 °C, 140 °C and 155 °C), and the slope of the compaction curve K 1, as an evaluation index, was statistically analyzed. The test specimens prepared using the appropriate compaction parameters were scanned by X-ray Computed Tomography (X-ray CT) and the air void distribution was analyzed by the Volume Graphics (VG) Studio MAX, which is for X-ray CT analysis that is used to calculate the volume distribution of the voids of an asphalt mixture. The results show that the SMA13 mixture exhibits a better compaction performance and temperature stability than the AC13 mixtures regardless of the asphalt binder type; The AC13 asphalt mixture has better temperature stability and compaction performance than the AC16 and AC20 asphalt mixture at the same number of gyrations, which with SK70# asphalt binder. The compaction temperature recommendations in Shaanxi Province are 140 °C for the AC13 mixtures whatever with SK70# or SK90# asphalt binder, 155 °C for the AC16 and AC20 gradation types with SK70# asphalt binder, 140 °C for the AC16 gradation types with SK90# asphalt binder, and 155 °C for the SMA13 mixtures with SK70# asphalt binder. Asphalt binder viscosity has a visible influence on the compaction level and VMA when the same gyration numbers are applied. For each recommended mixture, the volume of the majority of the air voids fell into the 0–150 mm 3 range, and most of these voids are concentrated in the 0–50 mm 3 volume range.